THE "DECAMERON" AND THE CHARACTERISTICS OF EASTERN LITERATURE - Vakhidova Mushtariy Uktamovna (American Journals, 2025)
The article analyzes Giovanni Boccaccio's "Decameron" from the perspective of comparative literature. The compositional structure of the work - the combination of a hundred short stories on a frame-plot basis - is compared with the traditions of "story within a story" characteristic of Eastern literature. The compositional methods and didactic endings of such Eastern narrative complexes as "One Thousand and One Nights", "Kalila and Dimna", "Totinoma" reveal similarities and differences in Boccaccio's poetics. Also, the images of a doctor, merchant, traveler, as well as intrigue and romantic plots found in the short stories shed light on the influence of the Eastern literary heritage on European literature. The article analyzes on a scientific basis how the work, combined with humanistic ideas, the glorification of love and criticism of the feudal-clerical system, served as a literary bridge between Eastern and Western cultures.
Keywords: Decameron, novella, frame-plot, One Thousand and One Nights, Kalila and Dimna, Totinoma, comparative literature, East-West literary relations.